2022
DOI: 10.3389/fphys.2022.913399
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Shexiang Tongxin Dropping Pills in a Swine Model of Coronary Slow Flow

Abstract: Objective: Preliminary clinical studies have confirmed that Shexiang Tongxin dropping pills (STDPs) could improve angina pectoris and attenuate vascular endothelial dysfunction in patients with slow coronary flow, but the underlying mechanism is not fully unclear. We aimed to investigate the impact of STDP in a swine model of coronary slow flow (SF) and related mechanisms.Methods: SF was induced by coronary injection of 40μm microspheres, and pigs were randomly divided into the SF group and SF plus STDP group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Current studies have found that the coronary flow reserve can be enhanced by drugs targeting the renin–angiotensin–aldosterone system, statins, calcium channel blockers, and ranolazine to minimize MACEs [ 81 86 ]. Some traditional Chinese medicines have also been used to treat CMD, including Shenmai injection and Shexiang Tongxin dropping pills, which may improve coronary microvascular function, endothelial function, and microvascular structure abnormalities by reducing oxidative stress, inflammatory response, and apoptosis [ 87 , 88 ]. In addition, CD34+ stem/progenitor cell therapy and neuropeptide-Y 1 receptor antagonists have been discovered to possess therapeutic potential for CMD [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have found that the coronary flow reserve can be enhanced by drugs targeting the renin–angiotensin–aldosterone system, statins, calcium channel blockers, and ranolazine to minimize MACEs [ 81 86 ]. Some traditional Chinese medicines have also been used to treat CMD, including Shenmai injection and Shexiang Tongxin dropping pills, which may improve coronary microvascular function, endothelial function, and microvascular structure abnormalities by reducing oxidative stress, inflammatory response, and apoptosis [ 87 , 88 ]. In addition, CD34+ stem/progenitor cell therapy and neuropeptide-Y 1 receptor antagonists have been discovered to possess therapeutic potential for CMD [ 89 , 90 ].…”
Section: Discussionmentioning
confidence: 99%